The Evaluation of 3-(2-Hydroxyphenyl)-1-Phenyl–Propenone as a Targeted Drug for Wound Healingin Sprague dawleyRats - Summaya M. Dhiyaaldeen (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study designed to evaluate the effects of 3-(2-Hydroxyphenyl)-1-phenyl–propenone (HPPP) as atargeted drug on enhancement the process of wound healing in Sprague dawley (SD) rats. A skin excisionwound was dissected from posterior neck area of each rat. Group 1 received no treatment, while group2 received Intrasite gel treatment. Wounds of groups 3 and 4 were dressed with HPPP 25 and 50 mg/kg, respectively. After 10 days, histological evaluation, immunohistochemistry and biochemical analysiswere investigated.Catalase (CAT), superoxide dismutase (SOD)enzymes and malondialdehyde (MDA)levels were determined in wound homogenates.Groups 3 and 4 showed remarkably a higher rate of woundhealing process when compared with the others. The microscopic results indicated increases in fibroblasts,collagen fibers and angiogenesis. Moreover, chalcone groups showed respectively an increase and reductionin antioxidant activity, and lipid peroxidation level. There were no signs of toxicity or mortality in the acutetoxicity experiment up to 1000 mg/kg.Our data provided an evidence for the first time that HPPP couldhasten significantly the wound healing process in rats.